1983
DOI: 10.1111/j.1348-0421.1983.tb00612.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Canine Distemper Viruses Adapted to Neural Cells and Their Neurovirulence in Mice

Abstract: Interaction of the Onderstepoort strain of canine distemper virus (CDV)with three established human neural cells, i.e. IMR-32 neuroblastoma, 118-MGC glioma and KG-I oligodendroglioma, was examined, and adaptation of CDV to these cells was also attempted. The unadapted virus was found to grow at relatively low titers in the three neural cells inducing moderate to minimal cytopathic effects (CPE). The virus was successfully grown at high titers in these cells after 8 to 10 passages. Biological characteristics su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
(21 reference statements)
0
14
0
Order By: Relevance
“…Variation in the H proteins was observed by peptide mapping, but not by 2-dimensional gel electrophoresis, in which H protein was not detected except for the MGC-virus. The absence of H proteins of the three viruses in 2-dimensional gel electrophoresis may be due to diffusion in the first dimension, because H proteins of these viruses have been clearly detected by SDS-PAGE (31). H proteins of measles virus, HN proteins of other paramyxoviruses are receptor-binding proteins in virus adsorption; F proteins of paramyxoviruses are responsible for the penetration of viruses into the cells and virus-induced cellfusion and hemolysis (4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Variation in the H proteins was observed by peptide mapping, but not by 2-dimensional gel electrophoresis, in which H protein was not detected except for the MGC-virus. The absence of H proteins of the three viruses in 2-dimensional gel electrophoresis may be due to diffusion in the first dimension, because H proteins of these viruses have been clearly detected by SDS-PAGE (31). H proteins of measles virus, HN proteins of other paramyxoviruses are receptor-binding proteins in virus adsorption; F proteins of paramyxoviruses are responsible for the penetration of viruses into the cells and virus-induced cellfusion and hemolysis (4).…”
Section: Discussionmentioning
confidence: 99%
“…By SDS-PAGE, the MW of viral proteins in infected cells among these adapted viruses has been found to be identical (31).…”
Section: Two-dimensional Gel Electrophoresis Of Virion Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such changes in neurovirulence after passage in different cells have been reported for canine distemper and rabies viruses. After adaptation of canine distemper virus to the same three human neural cells types used in this study, increased neurovirulence in mice was observed (Yoshikawa et al, 1983). Attenuated rabies virus was reported to show increased neurovirulence after a few passages in neuroblastoma cells, and it was speculated that randomly occurring virulent virus mutants replicated selectively in neuroblastoma cells (Clark, 1978(Clark, , 1980.…”
mentioning
confidence: 99%